Relative preference for the therapeutic approaches of G. A. Kelly and A. Ellis as a function of locus of control and of situational powerlessness. - Carey, Raymond P. (University of Ottawa (Canada), 1978)
This study examined relative preference for the cognitively oriented therapeutic approaches of Kelly and Ellis. Levels of locus of control and four treatment conditions depicting types of powerlessness situations served as independent variables. Participants were 215 upper division male college preparatory students from a Chicago Catholic high school. Internals, moderates and externals were randomly assigned to one of four treatment conditions and exposed to standardized written descriptions of the two therapeutic approaches. Following a comprehension test on the descriptions, an audio-taped mini-lesson on imaginative skills and muted-role taking was presented. After a practice trial, each treatment condition received a taped presentation depicting one of four types of powerlessness: in the face of personally significant others, bureaucratic-institutional others, personal fate or chance. Participants' responses to a research questionnaire were submitted to factor analyses to provide guidelines for subsequent scale construction. Three scales served as dependent measures: an alternatives-irrationalities scale, a preference scale and an experimenter-teacher scale. Analyses of variance performed on each of the scales yielded no statistically significant differences as a function of locus of control or of treatment conditions, nor were statistically significant interactions observed. Further statistical analysis revealed a significant preference for Kelly's approach both by all levels of locus of control as well as by all four treatment conditions. These findings were discussed and limitations on their interpretations were presented. Suggestions for future research were offered.
Keywords: Psychology, Clinical.